Distinctive clinical and histological characteristics of atrophic and hypertrophic facial photoageing. (30th December 2020) - Langton, A.K.; Ayer, J.; Griffiths, T.W.; Rashdan, E.; Naidoo, K.; Caley, M.P.; Birch‐Machin, M.A.; O'Toole, E.A.; Watson, R.E.B.; Griffiths, C.E.M.
Abstract: Background: Photoageing describes complex cutaneous changes which occur following chronic exposure to solar ultraviolet radiation (UVR). Amongst White Northern Europeans, facial photoageing appears as distinct clinical phenotypes: 'hypertrophic' photoageing (HP) and 'atrophic' photoageing (AP). Deep, coarse wrinkles predominate in individuals with HP, whereas those with AP have relatively smooth, unwrinkled skin with pronounced telangiectasia. AP individuals have an increased propensity for developing keratinocyte cancers. Objectives: To investigate whether histological differences underlie these distinct phenotypes of facial photoageing. Methods: Facial skin biopsies were obtained from participants with AP (10 M, 10 F; mean age: 78.7 years) or HP (10 M, 10 F; mean age: 74.5 years) and were assessed histologically and by immunohistochemistry. Results: Demographic characterization revealed 95% of AP subjects, as compared to 35% with HP, were Fitzpatrick skin type I/II; of these, 50% had a history of one or more keratinocyte cancers. There was no history of keratinocyte cancers in the HP cohort. Analysis of UVR‐induced mitochondrial DNA damage confirmed that all volunteers had received similar lifetime cumulative doses of sun exposure. Histologically, male AP had a significantly thicker epidermis than did AP females or those of either sex with HP. HP facial skin exhibited severe solar elastosis, whereas in AP facial skin, solar elastosis was apparent only in females. Loss of papillary dermal fibrillin‐rich microfibrils occurred in all HP and AP female subjects, but not in AP males. Furthermore, male AP had a significant reduction in collagen VII at the dermal–epidermal junction than did AP females or those of either sex with HP. Conclusions: This study provides further evidence that AP and HP represent distinct clinical and histological entities. Knowledge of these two phenotypes is clinically relevant due to the increased prevalence of keratinocyte cancers in those – particularly males – with the AP phenotype.